Amperometric L‐cysteine Sensor Using a Gold Electrode Modified with Thiolated Catechol. Issue 10 (28th July 2017) - Xu, Haitao; Li, Chaorong; Song, Dongcheng; Xu, Xiaolin; Zhao, Yan; Liu, Xiaoying; Su, Zhaohong
Abstract: A thiolated catechol (CA) consisting of 1, 6‐Hexanedithiol (HDT) and CA was modified on a gold (Au) electrode to obtain an amperometric L ‐cysteine sensor with detection limit of 60.6 nM. The preparation of thiolated CA was conducted via a thiol addition between HDT and electro‐oxidized CA (EOCA). Briefly, the thiol addition reaction was accomplished by potential cycling of HDT/Au electrode in 0.1 M phosphate buffer (PB, pH 7.2) containing CA, and an EOCA‐HDT/Au electrode was produced. The obtained EOCA‐HDT/Au electrode exhibits a pair of well‐defined redox peaks (at 0.22/0.10 V) of o ‐quinone moiety, which effectively mediates the oxidation of L ‐cysteine in a 0.1 M PB (pH 7.2), with an over‐potential decrease by ca. 0.12 V (versus bare Au electrode). Electrochemical quartz crystal microbalance, cyclic voltammetry and surface‐enhanced Raman spectra were used to study relevant processes and/or film properties. The amperometric L ‐cysteine sensor has good anti‐interferent ability and reproducibility. It also has acceptable recovery for detection of L ‐cysteine in urine samples. Abstract :